2020
DOI: 10.1016/j.jbusres.2019.08.026
|View full text |Cite
|
Sign up to set email alerts
|

When the performance comes into play: The influence of positive online consumer reviews on individuals' post-consumption responses

Abstract: Although the research on online consumer reviews (OCRs) is broad, several important gaps still exist. This paper aims to bridge some of these gaps by studying the influence of positive OCRs (pOCRs) on post-consumption responses, namely attitude toward the firm and repurchase intentions. It differentiates between whether the performance level during consumption was high or low, that is, whether the product met the objectives set by the consumers. To this end, the paper addresses pOCRs in a twofold approach. Fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 103 publications
(131 reference statements)
0
7
0
Order By: Relevance
“…We adapted these items from Pelletier et al (1998), which showed good reliability ( α = 0.73). To enhance the realism of the study, we included both textual descriptions and imagery in our manipulation (Hernández‐Ortega, 2020; Morales et al, 2017). Finally, we asked participants to respond to the same two manipulation checks regarding the manipulation content and the importance of their best friend as an activator of subjective norms.…”
Section: Methodsmentioning
confidence: 99%
“…We adapted these items from Pelletier et al (1998), which showed good reliability ( α = 0.73). To enhance the realism of the study, we included both textual descriptions and imagery in our manipulation (Hernández‐Ortega, 2020; Morales et al, 2017). Finally, we asked participants to respond to the same two manipulation checks regarding the manipulation content and the importance of their best friend as an activator of subjective norms.…”
Section: Methodsmentioning
confidence: 99%
“…They find that positive word-of-mouth reviews are related to longer survival for these stores. Hernández-Ortega (2020) finds there could be a U-shaped relationship between online consumer ratings and consumption. If the product does not meet the expectations of the consumer after reading the reviews, then they will decrease their consumption of the product.…”
Section: Theorymentioning
confidence: 98%
“…eWOM exists in online consumer opinion platforms, online communities and SNSs (Cheung and Lee, 2012; Litvin et al , 2008). eWOM in the form of online reviews include consumers' unbiased advice, opinions and comments (Hernández-Ortega, 2020). Online review is defined as “any positive, neutral, or negative online review about a product or service created and published on a consumer review website by a potential, former, or actual customer.” (Filieri, 2015, p. 1262).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Regarding review characteristics, studies have investigated the following: the effect of textual features (i.e. attribute salience, review valence and content concreteness) on the trustworthiness of consumer reviews (Huang and Liang, 2021); the impact of positive valence intensity on consumers' post consumption responses, namely, attitude and repurchase intention (Hernández-Ortega, 2020) and the influence of manifest/quantitative factors (i.e. review rating, word count and review length) and the latent/qualitative content factors (i.e.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation